If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = y + 7 Reorder the terms: 3 = 7 + y Solving 3 = 7 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 3 + -1y = 7 + y + -1y Combine like terms: y + -1y = 0 3 + -1y = 7 + 0 3 + -1y = 7 Add '-3' to each side of the equation. 3 + -3 + -1y = 7 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 7 + -3 -1y = 7 + -3 Combine like terms: 7 + -3 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4
| 2(4+n)= | | 2x+3=-5-2x | | 6a-6=20+4a | | 0.05x+0.2=0.03 | | 6x-15x/3-5=-11 | | X+[-5]=13 | | 1/2(8)(10) | | 5a-8=-63 | | 20t=1200 | | 2/3v=14 | | 7y-x=25 | | 21x/3-5=-11 | | (2/5)2 | | 4x+107+12=2x+75 | | 2v+7=w-3 | | (1/4)2 | | -8=6/-10 | | 9r+1=152 | | h(t)=-2t^2+9t | | 5(5)+3-5=4(5-1)+7 | | P=RTI | | 3x+30=-x+14 | | -3b+7-2=19 | | 128=17x+16 | | 2(x-5)=2(x-10) | | 4x^2-30=22 | | 4x-4.4=7.5 | | 9+y*3=21 | | 34.8/5.8 | | 5+9y=41 | | 128/3=x | | 6L+3=8L-11 |